MODEL SOCIAL NETWORK EFFECT ON PRODUCT DESIGN - Salayan, Madyunus; Panjaitan, Dedy Juliandri (ZERO: Jurnal Sains, Matematika dan Terapan, 2017)
The effect of social networking on business marketing strategies becomes inevitable. Taking a step back, we try to combine and analyze the effect on new product development and then propose a model for designing product deployment through social networks. We construct the issue of preferred stock (Kohli and Krishnamurti 1987), which is a common combinatorial optimization problem used as one of the methods for analyzing aggregated data analysis by marketers to identify products with the largest market share, and showing how to combine social networking securities in the issue of stock options .